1996
DOI: 10.1111/j.1559-1816.1996.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Communal Orientation and the Burnout Syndrome Among Nurses: A Replication and Extension1

Abstract: The present study focused on the distinction between two equity considerations in "people" jobs: the relationship with the recipients with whom one works and the exchange relationship with the organization for which one works. The sample consisted of nurses who were employed in one particular nursing home for mentally retarded patients. The results show that perceived inequity in both types of relationships is linked to emotional exhaustion and reduced personal accomplishment. As expected, individual differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 35 publications
7
87
1
4
Order By: Relevance
“…This sense of fair treatment then alleviates the detrimental effects of high job demands. Consistent with these premises, the literature also provides empirical evidence indicating that those employees perceiving organizational injustice are more likely to experience burnout and emotional exhaustion among service employees (Van Yperen, Buunk, & Schaufeli, 1992) and teachers (Van Horn et al, 1999). Likewise, the existence of fairness is found to be a valuable factor for coping with stress (Kroon, van de Voorde, & van Veldhoven, 2009) and preventing burnout (Noblet & Rodwell, 2009).…”
Section: Areas Of Worklife and Emotional Exhaustionsupporting
confidence: 55%
“…This sense of fair treatment then alleviates the detrimental effects of high job demands. Consistent with these premises, the literature also provides empirical evidence indicating that those employees perceiving organizational injustice are more likely to experience burnout and emotional exhaustion among service employees (Van Yperen, Buunk, & Schaufeli, 1992) and teachers (Van Horn et al, 1999). Likewise, the existence of fairness is found to be a valuable factor for coping with stress (Kroon, van de Voorde, & van Veldhoven, 2009) and preventing burnout (Noblet & Rodwell, 2009).…”
Section: Areas Of Worklife and Emotional Exhaustionsupporting
confidence: 55%
“…Another strength of the study is that two prominent theories of close relationships, Exchange Theory and Adult Attachment Theory, were used to help identify caregiving styles and the sources of caregiver attitudes. The study is able to add to a growing body of research finding that perceived inequities in relationships can have significant effects even in relationships where providing care is expected, such as long-term close relationships (Williamson and Schulz, 1990;Thompson et al, 1995;) and professional caregiving relationships (VanYperen et al, 1992). Furthermore, an overcontrolling caregiving style which was identified on the basis of attachment theory ideas (Kunce and Shaver, 1994) was found to be a significant correlate of caregiver resentment and patient perceptions of overprotection.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 89%
“…For instance, Garden (1989) found that burnout is associated with the Jungian "helping type", which is over-represented in the human services and is characterized by a need for affiliation, a capacity for warmth, and a desire for harmony (see Section 19.6.1). Furthermore, positive associations with burnout have been found with empathy (Williams, 1989) and with poor communal orientation; that is, with a low desire to give and receive benefits in response to the needs of others (Van Yperen et al, 1992; see also Section 19.6.2).…”
Section: Personality Characteristicsmentioning
confidence: 94%
“…Furthermore, the relationship between lack of reciprocity and burnout seems to be moderated by personality factors. For instance, Van Yperen et al (1992) found that nurses who felt they invested highly in the relationships with patients showed elevated levels of burnout only when they were low in communal orientation, a personality characteristic that refers to a general responsiveness to the needs of others. This finding was replicated by Van Yperen (1996).…”
Section: Burnout As a Lack Of Reciprocitymentioning
confidence: 98%